Abraham Kuyper en die reg op selfbeskikking van bevolkingsgroepe - Vyver, J. D. van der (Koers, 2006)
Abraham Kuyper and the right to self-determination of peoples Sphere sovereignty as a principle that regulates the mutual relationships among different social institutions originated from the philosophy of John Althusius, and this idea is found again in one form or another in the theories of various German political and legal philosophers. However, the descriptive name of this principle derives from the Dutch politician, Guillaume Groen van Prinsterer, who under the influence of Julius Stahl, confined the principle to church-state relationships. The special contribution of Abraham Kuyper was to extend sphere sovereignty to relationships among other social institutions. However, Kuyper did not distinguish precisely between the kinds of “circles” which in principle qualify for sphere sovereignty, and in the process he also included social communities among those with sphere sovereignty. An accurate distinction among social institutions that do qualify for sphere sovereignty and (unstructured) social communities that do not, derived from the philosophy of the cosmonomic idea of Herman Dooyeweerd. Kuyper’s perception of sphere sovereignty of social communities does correspond with the right to self-determination of ethnic, religious and linguistic communities as currently defined in international law. This right, however, does not include the right to secession from an existing state, but affords to the communities concerned the right to promote their culture, to testify to and practise their religion and to speak and apply their language without state interference.